Accounting Information and the Evaluation of Subordinate Performance: A Situational Approach. - Hirst, Mark K. (The Accounting Review, 1981)
Abstract ABSTRACT: This paper is concerned with the effect of different uses of accounting performance measures on the behavior of subordinates in different situations. It is argued that the incidence of dysfunctional behavior associated with different uses of accounting performance measures is a function of task uncertainty. The main hypotheses developed from the analysis are that a medium to high (medium to low) reliance on such measures minimizes the incidence of dysfunctional behavior in situations of low (high) task uncertainty. A number of subsidiary hypotheses are developed, and it is suggested that existing evidence is consistent with these hypotheses.